Health Insurance Coverage and Health Care Utilization: Evidence from the Affordable Care Act's Dependent Coverage Mandate - Baris K. Yörük (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper investigates the impact of the Affordable Care Act's (ACA's) dependent coverage mandate on health insurance coverage rates and health care utilization among young adults. Using data from the Medical Panel Expenditure Survey, I exploit the discontinuity in health insurance coverage rates at age 26, the new dependent coverage age cutoff enforced by the ACA. Under alternative regression discontinuity design models, I find that 2.5% to 5.3% of young adults lose their health insurance coverage once they turn 26. This effect is mainly driven by those who lose their private health insurance plan coverage and those who lose their health insurance plan coverage, whose main holder resides outside of the household. I also find that the discrete change in health insurance coverage rates at age 26 is associated with significant changes in office-based physician and dental visits, but does not have a significant impact on the utilization of outpatient or emergency department services. Furthermore, the effects of the ACA's dependent coverage mandate on health care spending and out-of-pocket costs are insignificant. These results are robust under alternative model specifications.
Keywords: I12; I13; I18; 330; affordable care act; health insurance coverage; health care utilization; dependent coverage